PERENCANAAN UNIT PENGOLAHAN LUMPUR DI INTALASI PENGOLAHAN AIR MINUM X KOTA SURABAYA - Rahayu, Septiya Rini; Pribadi, Arqowi; Nengse, Sulistiya; Setyowati, Rr. Diah Nugraheni; Utama, Teguh Taruna (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
Sludge of water treatment plant which contains aluminum if discharged directly into the water will be toxic. Due to not having a sludge treatment unit, water treatmet plant X dumped sludge from processing to the Surabaya River. In planning the stages of selecting alternative treatment units, the units will be selected to process sludge consisting of collecting tanks, gravity thickening, belt filter press, sludge filtrate storage tanks, supernatant tanks and dry cake storage containers. The amount of sludge volume produced by IPAM is 5875.475 m3 / day with an estimated procurement cost of Rp 3857,000,000.